Investor-state vs. state-state dispute settlement - Henrik Horn (Research Institute of Industrial Economics (IFN), 2018)
International investment agreements have provoked intense criticism in the policy debate during recent years. Particularly contentious has been their "ISDS" mechanisms, which enable investors to litigate against host countries. This paper examines whether host countries would be better off with state-state dispute settlement (SSDS), as often alleged, assuming that SSDS cause political/diplomatic litigation costs that are not present with ISDS. Two separate reasons why host countries might benefit from SSDS are identified, but neither provides a convincing argument for host countries to move to SSDS. The paper concludes that host countries should reduce the stringency of their agreements, rather than introduce imperfections in the dispute settlement systems to reduce their bite.
Keywords: F21; F23; F53; K33; 330; ISDS; Expropriation; International investment agreements; Regulatory chill